(untitled) (TEST Ticontre. Theory Text Translation, 2025)
The article aims to show the dialectic between remembering and forgetting within the post-exotic literature created by Antoine Volodine over the last forty years. Through the analysis of various works, this literature is interpreted as an attempt to re-elaborate the end of communist-oriented emancipation movements and to create the surrogate of a political action that has now become impossible: arising from the impracticability of the present with the aim of reconstructing the conditions of possibility for action in the future, it presents a transitory and subordinate character, functional to the transformation of melancholy into mourning, and therefore new life. L’articolo intende mostrare la centralità della dialettica tra memoria e oblio all’interno della letteratura post-esotica creata da Antoine Volodine nel corso degli ultimi quarant’anni. Grazie all’analisi di varie opere, tale letteratura viene interpretata come tentativo di rielaborare la fine dei movimenti di emancipazione di matrice comunista e di creare il surrogato di un’azione politica ormai divenuta impossibile: nascendo dall’impraticabilità del presente con il fine di ricostruire le condizioni di possibilità di un’azione futura, essa presenta un carattere transitorio e subordinato, funzionale alla trasformazione della malinconia per un mondo perduto in lutto, e quindi nuova vita.